Detection of Vibrio spp., Salmonella spp., and Shigella spp. among the frozen food samples employing enrichment culture technique (Stamford Journal of Microbiology, 2016)
Freezing has long been an established method for food preservation. Freezing temperature may act as a stress factor for microbial cells, transforming the cells into injured or dormant state. Upon inoculation, these debilitated cells cannot grow on solid media and hence produce false negative results. Foods contaminated with injured cells of pathogenic bacterial strains are of potential health risk. Employing enrichment cultivation technique, present study attempted to detect such injured, dormant or viable but non culturable (VBNC) cells in different frozen food samples, collected from local markets and super-shops of Dhaka metropolis. Compared to the conventional cultivation means, the enrichment procedure revealed a significant increase in bacterial burden as well as increase in the pathogenic load. A maximum of 3 log increase in case of total bacterial load while 4 log, 5 log and 2 log increase in case of Vibrio spp., Salmonella spp. and Shigella spp., consecutively were observed. These findings clearly demonstrated the presence of injured cells in frozen foods which could be lethal under normal condition thereby posing public health risk.Stamford Journal of Microbiology, Vol.5(1) 2015: 26-29